A Performance Optimized Operational Amplifier Using Transconductance Enhancement Topology Based on a-IGZO TFTs - Fanzhao Meng; Yi Li; Jun Li; Jie Liang; Jianhua Zhang (IEEE Journal of the Electron Devices Society)
This paper reports a performance optimized operational amplifier (OPAMP) using transconductance enhancement topology based on the amorphous indium- gallium-zinc-oxide (a-IGZO) thin-film transistors (TFTs). The performance of TFTs is enhanced by N2O plasma treatment that presents electrical characteristics suitable for accomplishing an OPAMP. The circuit consists of 19 TFTs with measured phase margin (PM) and unity-gain frequency (UGF) of 35.8° and 200 kHz, respectively. The DC power consumption (PDC) is 0.68 mW. Notably, it exhibits a high voltage gain (Av) of 32.67 dB and bandwidth (BW) of 15 kHz with 15 V DC supply voltage. Scarcely any work was reported with such a high gain while having a sufficient BW. The OPAMP demonstrates excellent performance among all a-IGZO literature and provides substantial support for the future development of TFT-based integrated circuits (ICs).